Frequent Sips of the Water for the Management of Gastroesophageal Reflux Induced Refractory Cough: A Case Report and Review of the Literature - Hassan Tariq; Jasbir Makker; Rafeeq Ahmed; Trupti Vakde; Harish Patel (Case Reports in Gastrointestinal Medicine)
Background. Chronic cough is often associated with gastroesophageal reflux disease (GERD). The role of gastroenterologist in the management of the chronic cough is to identify and manage GERD. Ineffective esophageal motility is often associated with GERD induced cough. Chronic cough is often refractory to medical and surgical management despite adequate acid control. Unresponsiveness warrants a thorough pulmonary evaluation. The pathophysiology of refractory cough in these patients is poorly understood, and hence management is often challenging. Case Presentation. A 75-year-old woman from Ghana was evaluated for GERD associated chronic cough. A 48-hour ambulatory pH study revealed acid exposure of 4.9% and high-resolution manometry showed decreased lower esophageal sphincter pressure, an inadequate response to medical and surgical management of GERD. Postfundoplication ambulatory pH testing demonstrated well-controlled acid reflux but her cough still persisted. Repeat manometry showed an ineffective motility disorder (IEM). Taking frequent sips of water eventually resolved her chronic cough. Conclusion. Frequent sips of water can be used in the management of the gastroesophageal reflux and ineffective motility induced cough. It results in increased esophageal clearance of acid, nonacid reflux, and ingested pharyngeal secretions, thus breaking the cycle of cough generated increased intra-abdominal pressure with reflux and more cough.